2017
DOI: 10.1002/cbf.3262
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol is associated with low frequency of interleukin 10–producing B cells in patients with atherosclerosis

Abstract: It is accepted that inflammation plays a critical role in the development of atherosclerosis; the pathogenesis is not clear. B-cell-produced interleukin (IL) 10 is an immune regulatory cytokine that can inhibit immune inflammation. This study tests a hypothesis that a psychological stress hormone, cortisol, suppresses IL-10 expression in peripheral B cells of patients with atherosclerosis. Peripheral blood samples were collected from patients with coronary artery atherosclerosis. B cells were isolated from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…Both IL-10 and TGF-β have been found to be essential for antigen-specific tolerogenic properties of adoptively transferred TIM-1 + Bregs ( 52 , 91 , 498 500 ). The regulatory nature of TIM-1 + B cells was further validated in different models, as the transfer of these cells can reduce the severity of allergic airway inflammation ( 91 ) and colitis ( 501 ), while promoting tumor growth ( 183 , 502 ). These results support a role of TIM-1 as an encompassing IL-10 + and TGF-β + Breg marker with functional implications.…”
Section: Tim-1-expressing Bregs (Tim-1 + Bregs)mentioning
confidence: 99%
“…Both IL-10 and TGF-β have been found to be essential for antigen-specific tolerogenic properties of adoptively transferred TIM-1 + Bregs ( 52 , 91 , 498 500 ). The regulatory nature of TIM-1 + B cells was further validated in different models, as the transfer of these cells can reduce the severity of allergic airway inflammation ( 91 ) and colitis ( 501 ), while promoting tumor growth ( 183 , 502 ). These results support a role of TIM-1 as an encompassing IL-10 + and TGF-β + Breg marker with functional implications.…”
Section: Tim-1-expressing Bregs (Tim-1 + Bregs)mentioning
confidence: 99%
“…rheumatic arthritis, which might aggravate these diseases (Sakkas et al, 2019). Huo et al (2017) reported that the increased level of serum cortisol was associated with the reduced presence of the IL-10-producing B cells (Bregs) in atherosclerotic patients. Currently, the therapeutic inducers of Bregs are promising drug discovery targets i.e.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Chronic psychological stress is associated with the pathogenesis of atherosclerosis, and serum cortisol might be a reference marker for this disease. Huo et al, showed that serum cortisol levels were higher in the patients with atherosclerosis than in healthy controls, and high plasma cortisol concentrations negatively correlated with circulating immuno-regulatory IL-10, promoting plaque destabilization ( 87 ). Chronic job-related stress leads to metabolic syndrome.…”
Section: Heart and Stress Systemmentioning
confidence: 99%